Edukasi Investasi dan Pencegahan Jeratan Pinjaman Ilegal bagi Masyarakat Pesisir Desa Sanur Kauh Denpasar Bali - I Gusti Agung Prabandari Tri Putri; Putu Gede Denny Herlambang; I Komang Sumerta; Octavianus Sumardana Pratama; Made Ayu Desy Geriadi; Sang Ayu Putu Nindia Antika (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2022)
This service program aims to provide education about investment and the dangers of illegal loans for the coastal communities of Sanur Kauh Village, Denpasar Bali. The method of implementing the service activity is socialization. The participants of the service activity consists of the Family Welfare Empowerment (PKK) groups including mothers, fishermen groups, and farmer business groups. Assistance is also provided to the community in terms of family financial management by a team of FEB UNR Lecturers. Evaluation of activities is carried out by distributing questionnaires to all participants for socialization and assistance. The results of this community service showed that 90 percent of participants felt that information on the legality of investment and the selection of legal and logical working capital financing institutions were very useful. The enthusiasm can be seen in the activeness of the participants in asking and answering questions asked by the speakers. This socialization activity is expected to be able to become the basis for making investment decisions and solving problems for people who need working capital. In the future, it is also hoped that the community will be able to implement effective and efficient financial management practices in their daily lives.